PENGARUH VOLUME PERDAGANGAN SAHAM DI MATURE MARKET TERHADAP VOLUME PERDAGANGAN SAHAM DI EMERGING MARKET - Astikawati, Yunita; Sore, Avelius Dominggus (Jurnal Pendidikan Ekonomi (JURKAMI), 2019)
Abstract:  Mature market is safer investment than emerging market. It’s became a references to emerging market in order to make investment decision particularly in stock exchange. Therefore, the analize to test of effect the stock trading volume in both mature market and emerging market year 2014 until 2018, is needed. The sample was determined by purposive sampling. Stock index which used in this research i.e. NYSE, NASDAQ, FTSE 100, SSEC, HANG SENG, Kopsi, STI, SENSEX, IHSG, JSE, Stock Exchange Thailand, and TSEC Taiwan. To analize the data is used multilinear regression. The result shows that’s mature market which representative by NYSE, Nasdaq, FTSE 100, SSEC, HANGSENG,  Kopsi, and STI has a significant positive effect to IHSG, SET, and TSEC. Meanwhile, NYSE, Nasdaq, FTSE 100, SSEC, HANGSENG, Kopsi, STI hasn’t stock trading volume effect in SENSEX and JSE. It can be concluded that in developing countries, the decision to buy and sell stock in the mature market became fundamental consideration for investors to sell or buy it. Keyword: Emerging, Mature, VolumeAbstrak: Mature market memiliki keamanan investasi daripada emerging market. Mature market menjadi acuan bagi emerging market dalam membuat keputusan investasi terutama di pasar modal. Oleh karena itu perlu adanya analisis untuk menguji pengaruh dari volume perdaganan saham di mature market dan emerging market tahun 2014-2018. Sampel yang digunakan adalah purposive sampling. Indek saham yang digunakan dalam analisis ini adalah NYSE, Nasdaq, FTSE 100, SSEC,  HANGSENG,  Kopsi, STI, SENSEX, IHSG, JSE, Stock Exchange Thailand, dan TSEC taiwan.  Analisis yang digunakan adalah regresi berganda. Hasil analisis menunjukan bawha mature market yang diwakili oleh indek NYSE, Nasdaq, FTSE 100, SSEC,  HANGSENG,  Kopsi, STI memiliki pengaruh positif signifikan  terhadap indek saham IHSG, SET, TSEC. Sedangkan indek NYSE, Nasdaq, FTSE 100, SSEC,  HANG SENG,  Kopsi, STI tidak mempengaruhi volume perdagangan saham di indek SENSEX dan JSE. Disimpulkan bahwa keputusan jual beli saham di mature market menjadi dasar pertimbangan bagi investor untuk menjual atau membeli saham pada negara berkembangKata Kunci: Emerging, Mature, Volume